A biologically active delivery material with dried-rehydrated vesicles containing the anti-inflammatory diclofenac for potential wound healing. (1st October 2016) - Ferreira, Helena; Silva, Raquel; Matamá, Teresa; Silva, Carla; Gomes, Andreia C.; Cavaco-Paulo, Artur
Abstract: Chronic wounds usually remain in the inflammatory phase of the healing process during several months or even years. Hence, a continuous research has been resulting in the development of wound dressings with improved performance. Herein, we report a delivery system for cutaneous wound healing, consisting of a textile material (non-woven gauzes) covered with lipidic vesicles containing diclofenac, a non-steroidal anti-inflammatory drug (NSAID). This study also aims to compare the entrapment efficiency data with previous works and confirm that this parameter and drug amount are not directly correlated. A method of dehydration–rehydration of the liposomes presenting different sizes and lamellarities was used to assess the best conditions to attain the highest drug entrapment efficiency. Optimum conditions for the NSAID release were achieved with high phospholipid concentrations and dried-rehydrated vesicles (DRVs) prepared from multilamellar liposomes (MLVs). A chemical activation of the gauzes was performed to enhance the vesicles attachment, also contributing to a higher drug amount in the surrounding media. In spite of the entrapment efficiency being lower comparatively with other values presented by us previously, the diclofenac concentration was considerably higher in this formulation. Entrapment efficiency is, therefore, not sufficient per se to define the real amount of drug contained in the formulation. The cytocompatibility assessment in human skin fibroblasts showed that DRVs from MLVs and DRVs from large unilamellar liposomes (LUVs) with less than 750 μM of egg-yolk phosphatidylcholine (EPC), containing diclofenac, were not cytotoxic after 72 h of contact, greatly implying potential for their application in the chronic wounds healing.